Adoptive transfer of immunity to Theileria parva in the CD8+ fraction of responding efferent lymph. - McKeever, D J (1994)
Evidence that class I major histocompatibility complex-restricted cytotoxic T lymphocytes (CTL) are involved in immunity to malaria has highlighted the potential importance of these cells in protection against intracellular parasites. Parasite-specific CTL are a prominent feature of the immune response of cattle to Theileria parva, a related apicomplexan parasite. The relationship between the appearance of these cells in the blood of immune cattle under challenge and the clearance of infection suggests that they are involved in the control of infection, but direct evidence is lacking that CTL can mediate protection. We have made a quantitative kinetic study of CTL responses in lymph originating from infected lymph nodes in a number of immune cattle under challenge with T. parva. Direct killing activity and the frequency of CTL precursors (CTLp) within responding cell populations were evaluated. A substantial increase in the proportion of CD8+ CTL was observed between days 8 and 11 after challenge. Frequencies of CTLp as high as 1:32 were observed and activity was essentially confined to the large blasting cell fraction. The analogous response in peripheral blood was of lower magnitude and delayed by 1-2 days. The high frequency of CTLp in efferent lymph permitted the adoptive transfer of this activity between immune and naive monozygotic twin calves. In separate experiments, naive calves lethally infected with T. parva were protected by inoculation of up to 10(10) responding CD8+ T cells derived from their immune twins. Elimination of CD8+ T cells within the inoculum abrogated this effect. These findings provide direct evidence that CD8+ T cells can control T. parva infections in immune cattle.